2000
DOI: 10.1063/1.126660
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between segregation-induced intergranular fracture and melting in the nickel–sulfur system

Abstract: The effect of S segregation to grain boundaries on the intergranular embrittlement of Ni has been studied at room temperature using Auger electron spectroscopy and slow strain rate tensile tests. The grain-boundary S concentration was varied by time-controlled annealing of dilute Ni–S alloy specimens at 625 °C. The ductile-to-brittle transition in Ni, as determined from percent integranular fracture and reduction-in-area measurements, occurred over a narrow range of S concentrations centered on 15.5±3.4 at. % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 9 publications
4
21
0
Order By: Relevance
“…A usually applied way to hinder the abnormal grain growth in electroplated nanomaterials is the codeposition of secondary-phase particles, such as SiC [13][14][15][16], or alloying with other elements [17][18][19][20][21][22]. It was found that even a little amount of impurities can improve the thermal stability [23][24][25][26] by segregating into the grain boundaries [10,11,[23][24][25]. The segregated elements decrease both the grain boundary mobility (through increasing the activation energy of grain boundary motion) [27][28][29][30] and the extra enthalpy stored in the grain boundaries [11,31].…”
Section: Introductionmentioning
confidence: 99%
“…A usually applied way to hinder the abnormal grain growth in electroplated nanomaterials is the codeposition of secondary-phase particles, such as SiC [13][14][15][16], or alloying with other elements [17][18][19][20][21][22]. It was found that even a little amount of impurities can improve the thermal stability [23][24][25][26] by segregating into the grain boundaries [10,11,[23][24][25]. The segregated elements decrease both the grain boundary mobility (through increasing the activation energy of grain boundary motion) [27][28][29][30] and the extra enthalpy stored in the grain boundaries [11,31].…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial chemistry also affects GB energy and mobility, and through this grain coarsening as well as the stability of nanostructures [10,11]. Local solute decoration can lead to the nucleation of second phases, formation of complexions [12], or selective melting of GBs [13]. Additionally, semiconductors are affected by GB segregation due to band structure changes that alter the recombination activity of charge carriers [14].Despite its enormous importance, GB segregation is far from being understood.…”
mentioning
confidence: 99%
“…The oxidation/sulfidation behavior documented for this Ni-Cr alloy in hydrogenated water was very similar to that found in higher temperature gaseous environments [22,23] where sulfur was discovered to first diffuse into grain boundaries forming Cr sulfides followed by oxidation reactions that release sulfur deeper into the material. Contrasting the results obtained for oxygen and sulfur cases is not only important for the general understanding of fundamental differences in solid-state electrochemistry of Ni-base alloys, but also because sulfur is a common contaminant in many service environments and an impurity in alloys [24][25][26]. In order to better understand the observed differences in grain boundary oxidation/sulfidation behavior of various Ni-base alloys, it is also important to examine how oxygen and sulfur atoms interact with both pristine and Ni surfaces doped with common alloying elements, an aspect that will be addressed in this study.…”
Section: Introductionmentioning
confidence: 94%